PELATIHAN MEDIA BELAJAR BERBASIS ONLINE DI ERA PANDEMI - Kartono Pinaryanto; Anastasia Rita Widiarti; Haris Sriwindono; Ridowati Gunawan; Hari Suparwito; Sri Hartati Wijono; Rosalia Arum Kumalasanti; Wiwien Widyastuti (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2022)
The education sector is one of the areas that has been most affected by the COVID-19 pandemic. Schools, which normally hold offline meetings, must now take place online. With this pandemic, the teaching process must be "forced" to be done online. The task model which is usually given in physical mode (questions on paper, done and collected) is no longer relevant to be done because of the limitations of physical meetings. On the other hand, students need an explanation from the teacher directly because they are used to the context of offline learning. Judging from the current level of smartphone ownership, whether owned by students themselves or their parents, we can use smartphone devices to help the teaching and learning process. But of course it requires technological literacy from the student side and the teacher side so that this teaching and learning process can be carried out properly. As a form of concern for the academic community of the Informatics Study Program at Sanata Dharma University to the problems that exist in the environment around the campus, we held training activities for making teaching media for State Elementary School of Timbulharjo teachers who ultimately played an important role in improving teachers' technological literacy in carrying out online learning. This activity had been carried out well offline in 2 stages, namely stage 1 on 9 and 10 June 2021 and stage 2 on 22 and 23 November 2021.